Musiques et stratégies de résistance culturelle des communautés afro-descendantes au Brésil : l’exemple du tambor de crioula et du tambor de mina, XIXe-XXIe siècle - Marie Cousin (Les Cahiers ALHIM)
This article provides a diachronic glimpse of how cultural resistance strategies have been developed in Afro-descendant communities during colonial, imperial, and republican Brazil. Indeed, the successive prohibitions and repressions led to the constitution of cultures of resistance which, by a surprising political turnaround during the twentieth century, became icons of regional and national identity. The tambor de crioula takes on this double identity, both a Brazilian intangible heritage since 2007, and the symbol of the historical memory of the resistance to slavery in black communities (quilombos). The tambor de mina, formerly described as "immoral" and "barbaric and fetishist" worship, has become that of "authentic Africanity". Anthropologists, touristic and cultural policies, and especially the fight of the associations specialized in the defense of the rights of descendants of the Maroons, were the actors of this revival, which also significates changes.